Tipologi Konsep Sistem Bank Sampah di Indonesia - A. Bayu adi pratama; Agam Marsoyo (President University, 2022)
In Indonesia, the waste bank is an urban infrastructure that is a solution to reduce the volume of waste that goes to the landfill (TPA). Various types of concepts that develop in the waste bank, make local residents more skilled in processing waste and can increase family income. In relation to concept innovations that have developed in several regions in Indonesia, one of the influencing factors is the perspective of the initiators who form the basis for the development of these concepts. The waste bank initiators have a perspective in responding to the concept that has been formed from the beginning of the emergence of the waste bank. The initiators aim to innovate in order to attract more customers in new ways.